Late Jurassic radiolarites in the sub-ophiolitic mélange of the Fruška Gora (NW Serbia) and their significance for the evolution of the Internal Dinarides - Stojadinovic, Uros; Djerić, Nevenka; Radivojević, Dejan; Krstekanić, Nemanja; Radonjić, Miloš; Džinić, Bojana (Ofioliti, 2022)
The Fruška Gora in north-western Serbia exposes the northernmost surface occurrences of ophiolites that derive from the obduction of the Vardar Ocean over the Adriatic continental margin. The late Oxfordian - early Kimmeridgian to late Kimmeridgian - early Tithonian radiolarians were determined from the blocks of radiolarites that constitute part of the sub-ophiolitic mélange along the southern flanks of the mountain. The newly obtained ages represent the youngest so-far determined radiolarites ages in this segment of the Dinarides. The mélange formation postdates the obtained ages of radiolarian assemblages, and it plausibly occurred during the latest Jurassic - earliest Cretaceous obduction-related thrusting in the Internal Dinarides.